2010
DOI: 10.1073/pnas.1010603107
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-dependent but acquired immunity-independent arthritis caused by DNA escaped from degradation

Abstract: DNase II digests the chromosomal DNA in macrophages after apoptotic cells and nuclei from erythroid precursors are engulfed. The DNase II-null mice develop a polyarthritis that resembles rheumatoid arthritis. Here, we showed that when bone marrow cells from the DNase II-deficient mice were transferred to the wildtype mice, they developed arthritis. A deficiency of Rag2 or a lack of lymphocytes accelerated arthritis of the DNase II-null mice, suggesting that the DNase II −/− macrophages were responsible for tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 42 publications
1
87
0
1
Order By: Relevance
“…Moreover, DNase II −/− Sting −/− do not exhibit signs of arthritis, similar to DNase II −/− Ifnar1 −/− mice (5, 7). Self-apoptotic DNA-triggered arthritis in such animals has been reported to be reminiscent of idiopathic arthritis or Still's disease in humans (18). STING has also been shown to rescue Trex1-mediated inflammation-related disorders in Trex1 −/− mice by mechanisms that remain unknown (19).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DNase II −/− Sting −/− do not exhibit signs of arthritis, similar to DNase II −/− Ifnar1 −/− mice (5, 7). Self-apoptotic DNA-triggered arthritis in such animals has been reported to be reminiscent of idiopathic arthritis or Still's disease in humans (18). STING has also been shown to rescue Trex1-mediated inflammation-related disorders in Trex1 −/− mice by mechanisms that remain unknown (19).…”
Section: Discussionmentioning
confidence: 99%
“…It is pertinent to mention that LITAF binding sites have been identified on several promoters of pro-and anti-inflammatory mediators (MCP-1, IL-6, and IL-10) in addition to TNF, suggesting that the reduced LPS-induced lethality and milder clinical and histological inflammatory arthritis (IA) features observed in tamLITAF(i) −/− mice may result from the decrease of activation of mediators regulated by LITAF. Indeed, using anti-IL-6 and anti-IL-1 receptor mABs, Kawane et al (28) were able to impede the "cytokine storm" and block joint swelling. Furthermore, Maia et al (29) used ArthroMAB to induce CAIA, and found that removing the cytoplasmic domain of CD248 impaired TNF-α-induced monocyte adhesion, underscoring the importance of regulating TNF-α production in rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that NETs are internalized through an endocytic mechanism leading to lysosomal degradation, as shown by blockage of NET clearance by a mixture of endocytosis inhibitors, accumulation of extranuclear DNA on CQ treatment, and colocalization of these extranuclear DNA dots within Lamp-1 vesicles and lysosomes. DNase II resides in the lysosomal compartment and has been shown to digest DNA from apoptotic cells, and Nagata and coworkers have reported that its deficiency leads to activation of the innate immune system (25,35). Macrophages from DNase IIdeficient mice accumulate undigested DNA, resulting in the production of TNF-a and polyarthritis (28).…”
Section: Discussionmentioning
confidence: 99%